2011
DOI: 10.1089/vim.2010.0116
|View full text |Cite
|
Sign up to set email alerts
|

Plasmids Enriched with CpG Motifs Activate Human Peripheral Blood Mononuclear CellsIn Vitroand Enhance Th-1 Immune Responses to Hepatitis B Surface Antigen in Mice

Abstract: T helper-1 (Th-1)-type immune responses play an important role in viral clearance during infection with hepatitis B virus (HBV). Unmethylated CpG motifs present in bacterial DNA can activate toll-like receptor 9 (TLR9) signals and act as potent adjuvants to induce Th-1-type immune responses. Here, a mini-plasmid with 812 base pairs in length was constructed and used as a vector to prepare a series of plasmids containing 3-21 copies of D-type CpG motifs. In vitro, these CpG-enriched plasmids strongly stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…These may elicit undesirable outcomes in an in vivo application [23]. Relative to mammalian genomic DNA, the occurrence of CpG dinucleotides in prokaryote-derived pDNA is overrepresented [24] and reportedly binds a member of the Toll-like family of receptors, eliciting a T cell-mediated immune response [25], [26], [27]. In addition, reducing the amounts of detrimental impurities, including bacterial genomic DNA and endotoxins, is critical for production of plasmids used in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…These may elicit undesirable outcomes in an in vivo application [23]. Relative to mammalian genomic DNA, the occurrence of CpG dinucleotides in prokaryote-derived pDNA is overrepresented [24] and reportedly binds a member of the Toll-like family of receptors, eliciting a T cell-mediated immune response [25], [26], [27]. In addition, reducing the amounts of detrimental impurities, including bacterial genomic DNA and endotoxins, is critical for production of plasmids used in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested a markedly increased number of IFN-γ-secreting CD8 + T cells, as well as CTL activity, in the Adv-HBcAg-TPPII group. Reports have suggested that T helper-1 (Th-1)-type immune responses are associated with viral clearance during infection with hepatitis B virus (HBV) [50], which may be important for HBV treatment. As shown above, Adv-HBcAg and Adv-HBcAg-TPPII significantly induced IL-2 and IFN-γ secretion, which indicated that Adv-HBcAg-TPPII triggers the Th1 immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CpG ODN treatments can enhance rHBsAg vaccine-induced immune responses and suppress HBV replication. [28][29][30] However, the goal of eradicating HBV without side effects has not yet been achieved. 31 Our data indicate that NP(HBV-CpG)-based therapy effectively aids in HBV clearance (Supporting Fig.…”
Section: Discussionmentioning
confidence: 99%
“…). Previous studies have shown that CpG ODN treatments can enhance rHBsAg vaccine‐induced immune responses and suppress HBV replication . However, the goal of eradicating HBV without side effects has not yet been achieved .…”
Section: Discussionmentioning
confidence: 99%